Berklee music theory: fundamentals of harmony book 2 - Schmeling, Paul (Hal Leonard, 2011)
The second in a two-volume series based on over 40 years of music theory instruction at Berklee College of Music. This volume focuses on harmony, including triads, seventh chords, inversions, and voice leading for jazz, blues and popular music styles. You'll develop the tools needed to write melodies and create effective harmonic accompaniments from a lead sheet. This revised edition includes an answer key for all exercises and lessons to check your progress. The price of this book includes access to audio tracks online, for download or streaming, using the unique code inside each book.